Elemental detection of fluorochemicals by nanospray-induced chemical ionization in afterglow of an inductively coupled plasma. Issue 4 (10th March 2022) - White, Samuel; Zheng, Kunyu; Tanen, Jordan; Lesniewski, Joseph E.; Jorabchi, Kaveh
Abstract : Post-plasma chemical ionization of ICP-produced HF by barium-based reagent ions vastly improves F detection sensitivity compared to that of ICP-MS where ions are formed inside the plasma. Abstract : Increased applications of fluorochemicals have prompted development of elemental methods for detection and quantitation of these compounds. However, high-sensitivity detection of fluorine is a challenge because of difficulties in excitation and ionization of this element. Recently, a new approach has emerged to detect F as a diatomic ion (BaF + ) in inductively coupled plasma mass spectrometry (ICP-MS). However, formation of this species in the high-temperature plasma is inefficient, leading to low sensitivities. Here, we introduce a post-ICP chemical ionization approach to enhance analytical performance for F detection in liquid samples. Solutions of fluorochemicals are introduced into an ICP leading to formation of HF in the afterglow. Subsequently, reagent ions from nanospray of sodium acetate and barium acetate electrolytes are utilized to ionize HF to Na2 F + and BaF +, respectively, via post-plasma ion-neutral reactions. Both ions provide substantially better sensitivities compared to that of BaF + formed inside the plasma in conventional ICP-MS methods. Notably, post-plasma BaF + offers a sensitivity of 280 cps ppb −1 for F, near two orders of magnitude higher than that of conventional ICP-MS methods. Compound-independent response for F from structurally diverse organofluorines is confirmed by monitoring BaF + and a limit of detection (LOD) of 8–11 ng mL −1 F is achieved. Importantly, isobaric interferences are substantially reduced in chemical ionization, leaving F background as the main factor in LOD determination. Insights into BaF + formation via experimental and computational investigations suggest that BaNO2 + and Ba(H2 O) n 2+ serve as reagent ions while nonreactive BaCH3 CO2 + is the dominant ion produced by nanospray. The facile development of effective post-plasma ionization chemistries using the presented approach offers a path for further improvements in F elemental analysis.